2023
DOI: 10.1002/advs.202306937
|View full text |Cite
|
Sign up to set email alerts
|

Intense Broadband Emission in the Unconventional 3D Hybrid Metal Halide via High‐Pressure Engineering

Xuening Sun,
Min Wu,
Xihan Yu
et al.

Abstract: Developing hybrid metal halides with self‐trapped exciton (STE) emission is a powerful and promising approach to achieve single‐component phosphors for wide‐color‐gamut display and illumination. Nevertheless, it is difficult to generate STEs and broadband emission in the classical and widely used 3D systems, owing to the great structural connectivity of metal‐halogen networks. Here, high pressure is implemented to achieve dual emission and dramatical emission enhancement in 3D metal halide of [Pb3Br4][O2C(CH2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…As illustrated in Figure e, the PL intensity exhibited a marginal increase below 8.0 GPa and then a substantial surge upon 10.5 GPa. This nonlinear continuous enhancement indicated a discontinuous change in the structure . Previous studies have demonstrated that the STE emission is influenced by the electron–phonon coupling, related to the crystal structural distortion of hybrid materials. , The multiple variations in the PL intensity indicated that there may be a structural phase transition with an intensified lattice distortion.…”
mentioning
confidence: 81%
“…As illustrated in Figure e, the PL intensity exhibited a marginal increase below 8.0 GPa and then a substantial surge upon 10.5 GPa. This nonlinear continuous enhancement indicated a discontinuous change in the structure . Previous studies have demonstrated that the STE emission is influenced by the electron–phonon coupling, related to the crystal structural distortion of hybrid materials. , The multiple variations in the PL intensity indicated that there may be a structural phase transition with an intensified lattice distortion.…”
mentioning
confidence: 81%